Desain High Temperature Gas-Cooled Reactor (HTGR) Model Geometri Heksagonal Dua Dimensi dengan Bahan Bakar Thorium Hasil Daur Ulang - Mutia Utari; Yanti Yulianti; Agus Riyanto (Departement of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2020)
The Research about the design of high temperature helium gas-cooled reactor (HTGR) terraces with thorium fuel recycled using the SRAC program has been completed. This research includes the percentage of fuel enrichment, reactor core size, reactor core configuration, criticality, and the distribution of the power density. The calculation of reactor core is done in two dimensions 16 hexagonal terrace section with a triangular mesh. The fuel is used, i.e. thorium with a burn-up of 20 GWd/t and 30 GWd/t, and helium gas as a cooler. The results obtained in this study show that the ideal HTGR reactor core design with reactor core size and configuration are (x) 22 cm at point (y) = 2035,05 cm and at (y) 11 cm at point (x) = 2035,05 cm, then enrichment in fuel 8%. The result of maximum power density is 550.3685 Watt/cm3 where the position at (x) = 22 cm and axis (y) = 11 with the effective multiplication factor value keff of 1,0000002.